2018
DOI: 10.1177/2325967118776635
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Quality of Evidence and Number of Citations in Top 50 Cited Articles in Rotator Cuff Repair Surgery

Abstract: Background:The number of article citations has been used as a measure for the impact of an article in the medical literature, with little emphasis on quality.Purpose:To (1) identify the top 50 most cited articles related to rotator cuff repair surgery, (2) determine whether there was a correlation between the top cited articles and level of evidence, and (3) determine whether there was a correlation between the top cited articles and study quality.Study Design:Cross-sectional study.Methods:The Web of Science a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
45
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(56 citation statements)
references
References 29 publications
8
45
3
Order By: Relevance
“…Additionally, only 2 of the prior studies examined the methodological quality of the most cited literature with regard to a specific pathology. 23,58 Corroborating what has been previously described, our findings show a continued need for emphasis on high-quality studies in terms of treatment of KD and MLKI in patients.…”
Section: Discussionsupporting
confidence: 82%
“…Additionally, only 2 of the prior studies examined the methodological quality of the most cited literature with regard to a specific pathology. 23,58 Corroborating what has been previously described, our findings show a continued need for emphasis on high-quality studies in terms of treatment of KD and MLKI in patients.…”
Section: Discussionsupporting
confidence: 82%
“…The reviewers used 3 scoring systems, selected to maintain consistency with similar bibliometric studies in other areas of orthopaedics. 25,41 The range of scores for each scoring system is listed in parentheses, with higher scores indicating higher methodological quality: the Modified Coleman Methodology Score (MCMS) 37 (0-100), the Jadad scale 26 (0-5), and the Methodological Index for Non-Randomized Studies (MINORS) 39 (0-24). The MCMS is a tool that accounts for the study design, methodology, and quality of outcome reporting, and its reliability has been validated with 99% reproducibility.…”
Section: Methodsmentioning
confidence: 99%
“…10 This study is the first to examine the relationship between quality and impact in Otolaryngology. 12 Nieminen et al also did not find a significant relationship between the quality of psychiatric research among four journals and the total number of citations per article over 9 years. However, they only used half the articles and the quality of the research was evaluated by the primary author using their own rubric.…”
Section: Discussionmentioning
confidence: 91%
“…Similar assessments have been performed in other medical specialties including orthopedic surgery, psychiatry and oral and maxillofacial surgery. Sochacki et al found no correlation between the level of evidence and the number of citations in the top 50 articles related to rotator cuff repair surgery 12 . Nieminen et al also did not find a significant relationship between the quality of psychiatric research among four journals and the total number of citations per article over 9 years.…”
Section: Discussionmentioning
confidence: 97%